Phytochemical Characterization, Functional Nutrition, and Anti-Diabetic Potentials of Leptadenia hastata (pers) Decne Leaves: In Silico and In Vitro Studies. Issue 16 (August 2022) - Chukwuma, Ifeoma Felicia; Nworah, Florence Nkechi; Apeh, Victor Onukwube; Omeje, Kingsley Ozioma; Nweze, Ekene John; Asogwa, Chukwudi Daniel; Ezeorba, Timothy Prince Chidike
The geometrical increase in diabetes mellitus (DM) and the undesirable side effects of synthetic drugs have intensified efforts to search for an effective and safe anti-diabetic therapy. This study aimed to identify the antioxidant and anti-diabetic agents in the ethanol extract of Leptadenia hastata (EELH). The phytochemicals, antioxidant vitamins, and minerals present in EELH were determined using standard procedures to achieve this aim. Gas chromatography coupled with mass spectroscopy and flame ionization detector (GC-MS/GC-FID) was employed to identify bioactive compounds. An e-pharmacophore model was generated from the extra precision, and energy-minimized docked position of standard inhibitor, acarbose onto human pancreatic amylase (HPA, PDB-6OCN). It was used to screen the GC-MS/GC-FID library of compounds. The top-scoring compounds were subjected to glide XP-docking and prime MM-GBSA calculation with the Schrodinger suite-v12.4. The Adsorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) prediction of the best-fit compounds was made using SwissADME and PROTOX-II webservers. Further validation of the docking results was performed with the in vitro analysis of the α-amylase and α-glucosidase inhibitory activities. EELH contains appreciable amounts of antioxidant and anti-diabetic phytoconstituents. The top-4 scoring compounds (rutin, epicatechin, kaempferol, and naringenin) from the EELH phytochemical library interacted with amino acid residues within and around the HPA active site. The ADMET prediction shows that epicatechin, kaempferol, and naringenin had favorable drug-likeness, pharmacokinetic properties, and a good safety profile. EELH demonstrated good inhibitory actions against α-amylase and α-glucosidase with 1C50 values of 14.14 and 4.22 µg/mL, respectively. Thus, L hastata phytoconstituents are promising novel candidates for developing an anti-diabetic drug.